Constitutional interpretation under the new South African order - Hofmeyr, Adriane Janet (My University, 2014)
This thesis explores the democratic legitimacy of the power of judicial review. It discounts the countermajoritarian dilemma on the basis that constitutional democracy means more than majoritarianism, it entails judicial protection of other characteristics fundamental to democracy from invasion even by a majority government. Such characteristics include political processes and values which ensure the continuation of democratic rule. The Court may, however, be criticised if it exercises its power of judicial review in a manner which is undemocratic. I argue that the Court is obliged to exercise its power in a manner which respects the doctrine of separation of powers. In interpreting the Constitution, the Court is therefore obliged to show deference to Parliament by giving effect to the purpose of a constitutional provision. I conclude that the Court may only have recourse to the values which the legislature chose to include in the Constitution, except when the Court protects those political processes and values which ensure the survival of constitutional democracy.
Thesis (LL.M.)--University of the Witwatersrand, Faculty of Law, 1998.
Keywords: purposive approach; countermajoritarian dilemma; separation of powers; fundamental rights; democracy; Constitutional law--South Africa